The use of the LandscapAR application as a pedagogical resource for geographical education - Oliveira, Érico Anderson de; Oliveira, Rosália Caldas Sanábio de (Geosaberes; Vol 10 No 22 (2019): Sept - DecDO - 10.26895/geosaberes.v10i22.805, 2019)
Connecting the new technologies  that  students already  ostensibly use to effective learning  is  a  challenge  for every  teacher  and  a  pedagogical asset  when  this linkage is  set. The theoretical basis was set up mainly on the precepts of Ausubel, Vygotsky and Piaget. The  chosen application "LandscapAR" transformation  of isolines captured by the mobile into 3D rendered images. The main objective was to verify the apprehension of the students in relation to the study of land relief and, particularly, of the level curves. The content was previously worked with the students, in Geography, of ten classes of the high school first year in the CEFET MG in the city of Belo Horizonte (MG). The activity with LandscapAr complemented the discussions, broadening the curiosity of students and making the cell phone a partner in the teaching-learning process.